A dealcoholized organic silicon sealant for photovoltaic modules
Through the introduction of modified nano -carbonate and fluorocarbon resin in the introduction of the introduction of co -silicon sealing gel in photovoltaic components, it solves the problem of insufficient damp -resistance performance in existing technologies, and achieves high -efficiency hygroscopic heat resistance.
Patent Information
- Application Number
- CN202411529753.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The silicone sealant for existing photovoltaic modules has average reliability under humid and heat conditions and is difficult to pass strict PCT testing, resulting in insufficient humidity and heat resistance.
The use of dehydrated organic silicon sealing gels are used to cover water talcium through modified nanoccal carbonate and fluorocarbon resin to introduce hydrophobic carbon fluoride bonds and fluoride -containing energy groups to enhance the film resistance of ultraviolet resistance and high temperature resistance.
The excellent humidity resistance performance of photovoltaic components with dehydrated organic silicon sealing can maintain good mechanical properties and durability under rigorous PCT conditions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to a dealcoholized organic silicon sealant for photovoltaic modules, belonging to the technical field of adhesives. Background Art
[0002] Photovoltaic power generation, as a new type of green energy, is now attracting more and more attention and promotion from all over the world. Photovoltaic conversion efficiency is the most important performance indicator in photovoltaic power generation. In addition to the influence of silicon cell quality, the sealing of the module is also a crucial factor. Due to its excellent aging resistance, silicone sealant is irreplaceable in the field of photovoltaic module sealing, which is more demanding and demanding in the environment.
[0003] The environmental tests that photovoltaic modules are subjected to outdoors mainly come from temperature changes, humidity, dust and sand in the atmosphere, sunlight, rain, wind, snow, etc. Due to its structural characteristics, room temperature curing dealcohol type silicone sealant has good aging resistance to high and low temperatures and ultraviolet rays, but its reliability is generally average under hot and humid conditions. Therefore, moisture and heat resistance is an important indicator for inspecting silicone sealants for photovoltaic modules. At present, materials used in photovoltaic modules mainly use DH (double 85 test), PCT, HAST and other tests to verify moisture and heat resistance. Among them, PCT conditions are the most stringent and the inspection efficiency is also higher. DH experiments often take 1000 hours, while PCT experiments generally take 24 hours to see obvious performance differences between different grades of materials.
[0004] Chinese patent CN107880797A discloses a high-strength silicone structural adhesive resistant to moisture and heat for photovoltaic modules, which is composed of component A and component B in a volume ratio of 10:1; wherein component A contains terminal hydroxyl polydimethylsiloxane, thixotropic agent, reinforcing filler, heat-resistant filler and plasticizer; component B is composed of terminal methyl polydimethylsiloxane, colorant carbon black, silane coupling agent, active hydrogen blocking agent, crosslinking agent, catalyst, antioxidant, light stabilizer and deep curing agent. The silicone structural adhesive obtained in this patent is a two-component silicone structural adhesive, which is not convenient to use. In addition, the moisture and heat resistance of the silicone structural adhesive in this patent has only been tested by DH (double 85 test) and has not been tested by the more stringent PCT test.
[0005] Chinese patent CN117467400A discloses a silicone adhesive for photovoltaic module frames and its preparation method and application. The silicone adhesive includes α,ω-dihydroxy polydimethylsiloxane, filler, pigment, silicone oil plasticizer, crosslinking agent, catalyst, coupling agent in a specific weight ratio; the structural formula of α,ω-dihydroxy polydimethylsiloxane is: the first type of filler is at least one of micron-sized light calcium carbonate, magnesium carbonate, magnesium hydroxide, calcium hydroxide, kaolin, and barium sulfate; the second type of filler is at least one of silicon / aluminum composite filler, silicon carbide / aluminum composite filler with specific thermal conductivity, graphite / copper composite filler with specific thermal conductivity, and carbon fiber / aluminum composite filler with specific thermal conductivity; the mass ratio of the first and second types of fillers is 2:1~18:1. The silicone adhesive obtained in this patent has only been tested by DH (double 85 test), and it cannot prove that the adhesive has very good moisture and heat resistance.
[0006] From the above, we can see that the silicone sealant used in photovoltaic modules still has the inherent defect of poor moisture and heat resistance, and it is difficult to pass the strict PCT test. Therefore, the development of a dealcoholized silicone sealant for photovoltaic modules with extremely excellent moisture and heat resistance will definitely have a huge driving effect on the long-term development of the photovoltaic industry. Summary of the invention
[0007] In view of the above-mentioned deficiencies in the prior art, the present invention provides a dealcoholized silicone sealant for photovoltaic modules to achieve the following invention objectives: to prepare a dealcoholized silicone sealant with extremely excellent moisture and heat resistance suitable for photovoltaic modules.
[0008] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0009] A dealcoholized organosilicon sealant for photovoltaic modules, wherein the specific formula of the dealcoholized organosilicon sealant for photovoltaic modules is, in parts by weight:
[0010] 170-240 parts of α,ω-dihydroxy polydimethylsiloxane,
[0011] 25~35 parts of modified nano calcium carbonate,
[0012] 30~55 parts of modified hydrotalcite,
[0013] Thickener 10~25 parts,
[0014] 1~3 parts of fumed silica,
[0015] 15-30 parts of dimethyl silicone oil,
[0016] Catalyst 0.2~1.5 parts,
[0017] 1~4 parts of co-catalyst,
[0018] Cross-linking agent 11~20 parts,
[0019] 8-15 parts of auxiliary cross-linking agent;
[0020] The fumed silica is Aerosil-R812 from Degussa, with a surface area of 260 m 2 / g, average particle size is 7nm;
[0021] The tackifier is one of bis(sec-butyl)orthosilicate triethylaluminum orthosilicate, tetra(2-methoxy-1-methylethyl) silicate, tetra(2-ethylbutyl) silicate, and tri(trimethylsilyl)borate;
[0022] The catalyst is dibutyltin dilaurate;
[0023] The co-catalyst is one of bis(trimethylsilylmethyl)amine and O-(trimethylsilyl)hydroxylamine;
[0024] The cross-linking agent is one of methylsilanetriol and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine;
[0025] The following are further improvements to the above technical solution:
[0026] Step 1: Preparation of modified nano calcium carbonate
[0027] After drying the nano-calcium carbonate at 110-135° C. for 10-20 hours, the nano-calcium carbonate is placed in a dry and water-free sealed high-speed dispersion kettle, and then anhydrous ethanol is added, the temperature is raised and kept constant at 60-80° C., and the speed is strongly dispersed at 7000-10000 rpm for 6-12 hours, and then the speed is reduced to 1500-3000 rpm, and then 3,3,3-trifluoropropyltriethoxysilane is added, and the temperature is kept constant for 8-15 hours, and then the temperature is lowered to room temperature for discharging, and the solid is centrifuged and dried in a vacuum oven at 60-75° C. for 5-11 hours to obtain modified nano-calcium carbonate;
[0028] The particle size of the nano calcium carbonate is 10-60 nm;
[0029] The mass ratio of the nano-calcium carbonate, anhydrous ethanol and 3,3,3-trifluoropropyltriethoxysilane is 25-45:150-190:3-9.
[0030] Step 2: Preparation of modified hydrotalcite
[0031] Fluorocarbon resin, toluene and triethylamine were added to the reaction kettle, and the stirring rate was controlled at 400-800 rpm. Under nitrogen protection, the temperature was raised and kept constant at 120-150°C. Hexamethyldisilazane was added to the kettle under condensation reflux and nitrogen protection. After the addition was completed, the reaction was continued at a constant temperature and stirred for 6-11 hours, and the temperature was lowered to obtain a silane-terminated fluorocarbon resin solution. Then, the hydrotalcite was dried at 120-140°C for 10-16 hours, and then added to the dispersion kettle. Toluene and brown were added to the kettle. Methyl palmitate, controlling the dispersion rate at 5000-9000 rpm, after intensive dispersion for 8-14 hours, raising the temperature in the kettle and keeping the temperature constant at 100-130°C, reducing the dispersion rate to 1000-3000 rpm, then adding the silane-terminated fluorocarbon resin solution, dispersing and stirring the reaction under condensation reflux for 6-13 hours, centrifuging, washing the separated solid with anhydrous ethanol for 3-5 times, and drying it in a vacuum oven at 50-80°C for 6-13 hours to obtain the modified hydrotalcite;
[0032] The fluorocarbon resin has a fluorine content of 30-40 wt %, a number average molecular weight of 1000-4000 g / mol, a viscosity of 200-900 mPa·s, a hydroxyl value of 40-65 mgKOH / g, and an acid value of 1.0-2.5 mgKOH / g;
[0033] In the preparation of the silane-terminated fluorocarbon resin solution, the mass ratio of fluorocarbon resin, toluene, triethylamine, and hexamethyldisilazane is 15-40:140-240:1-4:3-8;
[0034] The particle size of the hydrotalcite is 30-100 nm;
[0035] The mass ratio of the hydrotalcite, toluene, methyl palmitate and silane-terminated fluorocarbon resin solution is 30-60:50-140:1-5:40-100.
[0036] Step 3: Preparation of cross-linking agent
[0037] Add diethylenetriamine and acetone to a reaction kettle, then heat and maintain the temperature at 40-60°C, control the stirring rate at 300-600 rpm, and then drip 3-isocyanatepropyltrimethoxysilane into the reaction kettle at a rate of 1-10 g / min under stirring and condensing reflux. After the dripping is completed, continue to stir and react at a constant temperature for 5-11 hours, continue to maintain the constant temperature, vacuum distill under reduced pressure, and evaporate the acetone to obtain a solid that is a co-crosslinking agent;
[0038] The mass ratio of the diethylenetriamine, acetone and 3-isocyanatepropyltrimethoxysilane is 15-45:110-270:8-26.
[0039] Step 4: Preparation of dealcoholized silicone sealant
[0040] According to the specific formula of dealcoholization type silicone sealant for photovoltaic modules in parts by weight, α, ω-dihydroxy polydimethylsiloxane, tackifier, dimethyl silicone oil, catalyst, co-catalyst, cross-linking agent and co-cross-linking agent are put into a dry and water-free double planetary mixer, and the vacuum negative pressure in the double planetary mixer is maintained at -0.1~-0.09MPa. The stirring rate is controlled at 90~130 rpm and the dispersion rate is 6000~8500 rpm. After stirring and dispersing for 1~3 hours, the stirring rate is increased to 140~180 rpm and the dispersion rate is increased to 9000~10000 rpm, and then fumed silica is added. After stirring and dispersing for 5~8 hours, modified nano calcium carbonate and modified hydrotalcite are added, and stirring and dispersing is continued for 6~12 hours to obtain a viscous glue solution. After continuous vacuum degassing, the bubble-free glue solution is discharged and filled into a dry packaging container, filled with nitrogen for protection and sealed, which is the dealcoholization type silicone sealant for photovoltaic modules.
[0041] Compared with the prior art, the present invention achieves the following beneficial effects:
[0042] 1. The present invention introduces carbon-fluorine bonds and fluorine-containing functional groups with excellent hydrophobicity into the formula of dealcoholized silicone sealant by using fluorine-containing siloxane 3,3,3-trifluoropropyltriethoxysilane to modify the surface of nano-calcium carbonate and fluorocarbon resin to coat hydrotalcite. This makes the cured dealcoholized silicone sealant have strong overall hydrophobicity from the inside to the outside. In addition, the fluorine-containing organic chemical bonds and fluorine-containing functional groups have excellent ultraviolet resistance and high temperature and humidity resistance. Therefore, the carbon-fluorine bonds and fluorine-containing functional groups introduced by the above two methods can greatly improve the ultraviolet resistance and high temperature and humidity resistance of the dealcoholized silicone sealant.
[0043] 2. The present invention uses 3,3,3-trifluoropropyltriethoxysilane to perform surface modification on nano calcium carbonate, and uses fluorocarbon resin to perform coating modification on hydrotalcite, which can fully ensure the uniform dispersion of nano calcium carbonate and nano hydrotalcite in the dealcoholization type silicone sealant formula system, thereby making the enhancement effect of nano calcium carbonate and hydrotalcite on the dealcoholization type silicone sealant and the improvement effect of ultraviolet resistance, high temperature resistance and high humidity resistance reach a higher level;
[0044] 3. In the process of coating hydrotalcite with fluorocarbon resin, the present invention partially caps the fluorocarbon resin with hexamethyldisilazane. The silicon-hydrogen bonds and nitrogen-hydrogen bonds contained in hexamethyldisilazane have very high reactivity. By capping with hexamethyldisilazane, the high reactivity of silicon-hydrogen bonds and nitrogen-hydrogen bonds can be utilized to ensure the coating effect of the fluorocarbon resin on the hydrotalcite, that is, the fluorocarbon resin is not only coated on the surface of the hydrotalcite in a physical adsorption manner, but also chemically bonded with the surface of the hydrotalcite to achieve chemical adsorption and coating on the surface of the hydrotalcite. In addition, a part of the silicon-hydrogen bonds and nitrogen-hydrogen bonds that have not reacted completely can act as a crosslinking agent in the curing process of the dealcoholized silicone sealant, so that the modified hydrotalcite can enter the three-dimensional crosslinked network of the silicone sealant in a chemical crosslinking bonding manner, and then the hydrotalcite can maximize the enhancement and toughening of the silicone sealant and the improvement of the UV resistance and high temperature and high humidity resistance.
[0045] 4. The tackifier added in the present invention, namely, bis(sec-butyl)orthosilicate triethylaluminum orthosilicate, tetra(2-methoxy-1-methylethyl) silicate, tetra(2-ethylbutyl) silicate, tri(trimethylsilyl)borate, are all hydrolysis-sensitive silane organic substances, which can undergo hydrolysis reaction with a very small amount of moisture in the air, thereby enhancing the adhesion between the dealcoholization type silicone sealant and the substrate, and playing a role in increasing the viscosity. At the same time, the above-mentioned silane organic substances have relatively high functionality and a considerable degree of cross-linking reaction ability, so they have a certain contribution to improving the cross-linking density of the adhesive layer after curing, thereby also being able to improve the mechanical properties and UV resistance, high temperature and high humidity resistance of the dealcoholization type silicone sealant;
[0046] 5. The auxiliary cross-linking agent obtained by reacting diethylenetriamine and 3-isocyanatepropyltrimethoxysilane, and the added two cross-linking agents, methylsilanetriol and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine, have ultra-high functionality and extremely high cross-linking reaction activity. At the same time, because the auxiliary cross-linking agent contains a negatively charged tertiary amine molecular structure, the tertiary amine molecular structure has a certain self-catalytic effect, which can catalyze the cross-linking reaction between α,ω-dihydroxypolydimethylsiloxane and the cross-linking agent and the auxiliary cross-linking agent, thereby improving the activity of the cross-linking reaction and the thoroughness of the reaction. In addition, the self-catalytic effect of the auxiliary cross-linking agent will cooperate with the catalytic effect of the two auxiliary catalysts, bis(trimethylsilylmethyl)amine and O-(trimethylsilyl)hydroxylamine, and the dibutyltin dilaurate catalyst to improve the overall reaction rate and the thoroughness of the curing reaction of the adhesive layer, so that the cured adhesive layer finally has excellent mechanical properties and extremely excellent UV resistance and moisture and heat resistance.
[0047] 6. The dealcoholized silicone sealant for photovoltaic modules obtained by the present invention has a surface drying time of 13-16 min, a 24-hour curing depth of 4.8-5.3 mm, an adhesive strength of 2.5-2.8 MPa, a tensile strength of 3.0-3.5 MPa, a shear strength of 2.0-2.5 MPa, an elongation at break of 387-413%, a Shore hardness of 52-56, and UV resistance with an adhesive strength retention rate of 98-99%, a tensile strength retention rate of 96-98%, and an elongation at break retention rate of 95-99%. The moisture and heat resistance performance (24 hours) has an adhesive strength retention rate of 93-95%, a tensile strength retention rate of 91-94%, and an elongation at break retention rate of 91-93%. The moisture and heat resistance performance (48 hours) has an adhesive strength retention rate of 85-88%, a tensile strength retention rate of 84-89%, and an elongation at break retention rate of 83-86%. DETAILED DESCRIPTION
[0048] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0049] Example 1: A dealcoholized silicone sealant for photovoltaic modules
[0050] Step 1: Preparation of modified nano calcium carbonate
[0051] After drying the nano-calcium carbonate at 125° C. for 16 hours, the nano-calcium carbonate is placed in a dry and water-free sealed high-speed dispersion kettle, and then anhydrous ethanol is added, the temperature is raised and kept constant at 68° C., and after strong dispersion at a speed of 7800 rpm for 9 hours, the speed is reduced to 1900 rpm, and then 3,3,3-trifluoropropyltriethoxysilane is added, and the temperature is kept constant for 11 hours, and then the temperature is reduced to room temperature for discharge, and centrifugation is performed. After the obtained solid is dried in a vacuum oven at 65° C. for 8 hours, the modified nano-calcium carbonate is obtained;
[0052] The particle size of the nano calcium carbonate is 50 nm;
[0053] The mass ratio of the nano calcium carbonate, anhydrous ethanol and 3,3,3-trifluoropropyltriethoxysilane is 30:165:7.
[0054] Step 2: Preparation of modified hydrotalcite
[0055] Fluorocarbon resin, toluene and triethylamine were added to a reaction kettle, and the stirring rate was controlled to 700 rpm, and the temperature was raised and kept constant at 140°C under nitrogen protection. Hexamethyldisilazane was added to the kettle under nitrogen protection while condensing and refluxing. After the addition was completed, the reaction was continued at a constant temperature and stirred for 9 hours, and the temperature was lowered to obtain a silane-terminated fluorocarbon resin solution. Then, the hydrotalcite was dried at 135°C for 14 hours, and then added to a dispersion kettle. Toluene and methyl palmitate were then added to the kettle, and the dispersion rate was controlled to 8000 rpm. After strong dispersion for 12 hours, the temperature in the kettle was raised and kept constant at 120°C, and the dispersion rate was reduced to 2500 rpm. Then, the silane-terminated fluorocarbon resin solution was added, and the reaction was dispersed and stirred under condensation and reflux for 11 hours, and then centrifuged. The separated solid was washed with anhydrous ethanol for 4 times, and then dried in a vacuum oven at 60°C for 8 hours to obtain a modified hydrotalcite.
[0056] The fluorocarbon resin has a fluorine content of 36 wt %, a number average molecular weight of 3000 g / mol, a viscosity of 700 mPa·s, a hydroxyl value of 60 mgKOH / g, and an acid value of 2 mgKOH / g;
[0057] In the preparation of the silane-terminated fluorocarbon resin solution, the mass ratio of fluorocarbon resin, toluene, triethylamine, and hexamethyldisilazane is 30:190:2:6;
[0058] The particle size of the hydrotalcite is 70 nm;
[0059] The mass ratio of the hydrotalcite, toluene, methyl palmitate and silane-terminated fluorocarbon resin solution is 50:100:2:80.
[0060] Step 3: Preparation of cross-linking agent
[0061] Add diethylenetriamine and acetone to a reaction kettle, then heat and maintain the temperature at 55°C, control the stirring rate to 500 rpm, stir under condensation reflux, then drop 3-isocyanatepropyltrimethoxysilane into the reaction kettle at a rate of 6 g / min, after the dropwise addition is completed, continue to stir at a constant temperature for 9 hours, continue to maintain the constant temperature, evacuate and distill under reduced pressure, and after evacuating to remove acetone, the obtained solid is the auxiliary cross-linking agent;
[0062] The mass ratio of the diethylenetriamine, acetone and 3-isocyanatepropyltrimethoxysilane is 35:220:16.
[0063] Step 4: Preparation of dealcoholized silicone sealant
[0064] The specific formula of the dealcoholized organic silicon sealant for photovoltaic modules is as follows, in parts by weight:
[0065] 210 parts of α,ω-dihydroxy polydimethylsiloxane,
[0066] 33 parts of modified nano calcium carbonate,
[0067] 45 parts of modified hydrotalcite,
[0068] 15 parts of tackifier,
[0069] 2 parts of fumed silica,
[0070] 18 parts of dimethyl silicone oil,
[0071] 0.8 parts of catalyst,
[0072] 2 parts of co-catalyst,
[0073] 17 parts of cross-linking agent,
[0074] 12 parts of auxiliary cross-linking agent;
[0075] The fumed silica is Aerosil-R812 from Degussa, with a surface area of 260 m 2 / g, average particle size is 7nm;
[0076] The tackifier is bis(sec-butyl)orthosilicate triethyl aluminum orthosilicate;
[0077] The catalyst is dibutyltin dilaurate;
[0078] The co-catalyst is bis(trimethylsilylmethyl)amine;
[0079] The cross-linking agent is methylsilanetriol;
[0080] According to the specific formula of dealcoholization type silicone sealant for photovoltaic modules in parts by weight, α, ω-dihydroxy polydimethylsiloxane, tackifier, dimethyl silicone oil, catalyst, co-catalyst, cross-linking agent and co-cross-linking agent are put into a dry and water-free double planetary mixer, and the vacuum negative pressure in the double planetary mixer is maintained at -0.093. Under the conditions of controlling the stirring rate at 100 rpm and the dispersion rate at 8000 rpm, after stirring and dispersing for 2 hours, the stirring rate is increased to 150 rpm and the dispersion rate is increased to 9600 rpm, and then fumed silica is added. After stirring and dispersing for 6 hours, modified nano calcium carbonate and modified hydrotalcite are added, and stirring and dispersing is continued for 11 hours to obtain a viscous glue solution. After continuous vacuum degassing, the bubble-free glue solution is discharged and filled into a dry packaging container, which is filled with nitrogen for protection and sealed to obtain the dealcoholization type silicone sealant for photovoltaic modules.
[0081] Example 2: A dealcoholized silicone sealant for photovoltaic modules
[0082] Step 1: Preparation of modified nano calcium carbonate
[0083] After drying the nano calcium carbonate at 110°C for 10 hours, the nano calcium carbonate is placed in a dry and water-free sealed high-speed dispersion kettle, and then anhydrous ethanol is added, the temperature is raised and kept constant at 60°C, and after intensive dispersion at a speed of 7000 rpm for 6 hours, the speed is reduced to 1500 rpm, and then 3,3,3-trifluoropropyltriethoxysilane is added, and the reaction is kept constant for 8 hours, and then the temperature is reduced to room temperature, the material is discharged, and centrifuged, and the obtained solid is dried in a vacuum oven at 60°C for 5 hours to obtain modified nano calcium carbonate;
[0084] The particle size of the nano calcium carbonate is 10 nm;
[0085] The mass ratio of the nano calcium carbonate, anhydrous ethanol and 3,3,3-trifluoropropyltriethoxysilane is 25:150:3.
[0086] Step 2: Preparation of modified hydrotalcite
[0087] Fluorocarbon resin, toluene and triethylamine were added to a reaction kettle, and the stirring rate was controlled at 400 rpm. Under nitrogen protection, the temperature was raised and kept constant at 120°C, and hexamethyldisilazane was added to the kettle under condensation and reflux. After the addition was completed, the reaction was continued at a constant temperature and stirred for 6 hours, and the temperature was lowered to obtain a silane-terminated fluorocarbon resin solution. Then, the hydrotalcite was dried at 120°C for 10 hours, and then added to a dispersion kettle. Toluene and methyl palmitate were then added to the kettle, and the dispersion rate was controlled at 5000 rpm. After strong dispersion for 8 hours, the temperature in the kettle was raised and kept constant at 100°C, and the dispersion rate was reduced to 1000 rpm. Then, the silane-terminated fluorocarbon resin solution was added, and the reaction was dispersed and stirred under condensation and reflux for 6 hours, and then centrifuged. The separated solid was washed with anhydrous ethanol for 3 times, and then dried in a 50°C vacuum oven for 6 hours to obtain a modified hydrotalcite.
[0088] The fluorocarbon resin has a fluorine content of 30 wt %, a number average molecular weight of 1000 g / mol, a viscosity of 200 mPa·s, a hydroxyl value of 40 mgKOH / g, and an acid value of 1.0 mgKOH / g;
[0089] In the preparation of the silane-terminated fluorocarbon resin solution, the mass ratio of fluorocarbon resin, toluene, triethylamine, and hexamethyldisilazane is 15:140:1:3;
[0090] The particle size of the hydrotalcite is 30 nm;
[0091] The mass ratio of the hydrotalcite, toluene, methyl palmitate and silane-terminated fluorocarbon resin solution is 30:50:1:40.
[0092] Step 3: Preparation of cross-linking agent
[0093] Add diethylenetriamine and acetone to a reaction kettle, then heat and maintain the temperature at 40°C, control the stirring rate to 300 rpm, stir under condensation reflux, then drop 3-isocyanatepropyltrimethoxysilane into the reaction kettle at a rate of 1 g / min, after the dropwise addition is completed, continue to stir at a constant temperature for 5 hours, continue to maintain the constant temperature, evacuate and distill under reduced pressure, and after evacuating to remove acetone, the obtained solid is the auxiliary cross-linking agent;
[0094] The mass ratio of the diethylenetriamine, acetone and 3-isocyanatepropyltrimethoxysilane is 15:110:8.
[0095] Step 4: Preparation of dealcoholized silicone sealant
[0096] The specific formula of the dealcoholized organic silicon sealant for photovoltaic modules is as follows, in parts by weight:
[0097] 170 parts of α,ω-dihydroxy polydimethylsiloxane,
[0098] 25 parts of modified nano calcium carbonate,
[0099] 30 parts of modified hydrotalcite,
[0100] Thickener 10 parts,
[0101] 1 part of fumed silica,
[0102] 15 parts of dimethyl silicone oil,
[0103] 0.2 parts of catalyst,
[0104] 1 part of co-catalyst,
[0105] 11 parts of cross-linking agent,
[0106] 8 parts of auxiliary cross-linking agent;
[0107] The fumed silica is Aerosil-R812 from Degussa, with a surface area of 260 m 2 / g, average particle size is 7nm;
[0108] The tackifier is tetrakis(2-methoxy-1-methylethyl) silicate;
[0109] The catalyst is dibutyltin dilaurate;
[0110] The co-catalyst is O-(trimethylsilyl)hydroxylamine;
[0111] The cross-linking agent is N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine;
[0112] According to the specific formula of dealcoholization type silicone sealant for photovoltaic modules in parts by weight, α, ω-dihydroxy polydimethylsiloxane, tackifier, dimethyl silicone oil, catalyst, co-catalyst, cross-linking agent and co-cross-linking agent are put into a dry and water-free double planetary mixer, and the vacuum negative pressure in the double planetary mixer is maintained at -0.1MPa. The stirring rate is controlled at 90 rpm and the dispersion rate is 6000 rpm. After stirring and dispersing for 1 hour, the stirring rate is increased to 140 rpm and the dispersion rate is increased to 9000 rpm, and then fumed silica is added. After stirring and dispersing for 5 hours, modified nano calcium carbonate and modified hydrotalcite are added, and stirring and dispersing is continued for 6 hours to obtain a viscous glue solution. After continuous vacuum degassing, the bubble-free glue solution is discharged and filled into a dry packaging container, which is filled with nitrogen for protection and sealed to obtain the dealcoholization type silicone sealant for photovoltaic modules.
[0113] Example 3: A dealcoholized silicone sealant for photovoltaic modules
[0114] Step 1: Preparation of modified nano calcium carbonate
[0115] After drying the nano calcium carbonate at 135°C for 20 hours, the nano calcium carbonate is placed in a dry and water-free sealed high-speed dispersion kettle, and then anhydrous ethanol is added, the temperature is raised and kept constant at 80°C, and after strong dispersion at a speed of 10,000 rpm for 12 hours, the speed is reduced to 3,000 rpm, and then 3,3,3-trifluoropropyltriethoxysilane is added, and the reaction is continued at a constant temperature for 15 hours, and then the temperature is reduced to room temperature for discharge, and centrifugation is performed. The obtained solid is dried in a vacuum oven at 75°C for 11 hours to obtain modified nano calcium carbonate;
[0116] The particle size of the nano calcium carbonate is 60nm;
[0117] The mass ratio of the nano calcium carbonate, anhydrous ethanol and 3,3,3-trifluoropropyltriethoxysilane is 45:190:9.
[0118] Step 2: Preparation of modified hydrotalcite
[0119] Fluorocarbon resin, toluene and triethylamine were added to a reaction kettle, and the stirring rate was controlled at 800 rpm. Under nitrogen protection, the temperature was raised and kept constant at 150°C. Hexamethyldisilazane was added to the kettle under condensation and reflux. After the addition was completed, the reaction was continued at a constant temperature and stirred for 11 hours, and the temperature was lowered to obtain a silane-terminated fluorocarbon resin solution. The hydrotalcite was then dried at 140°C for 16 hours and added to a dispersion kettle. Toluene and methyl palmitate were then added to the kettle. The dispersion rate was controlled at 9000 rpm. After strong dispersion for 14 hours, the temperature in the kettle was raised and kept constant at 130°C. The dispersion rate was reduced to 3000 rpm. The silane-terminated fluorocarbon resin solution was then added. The reaction was dispersed and stirred under condensation and reflux for 13 hours, and then centrifuged. The separated solid was washed with anhydrous ethanol for 5 times, and then dried in a vacuum oven at 80°C for 13 hours to obtain a modified hydrotalcite.
[0120] The fluorocarbon resin has a fluorine content of 40 wt %, a number average molecular weight of 4000 g / mol, a viscosity of 900 mPa·s, a hydroxyl value of 65 mgKOH / g, and an acid value of 2.5 mgKOH / g;
[0121] In the preparation of the silane-terminated fluorocarbon resin solution, the mass ratio of fluorocarbon resin, toluene, triethylamine, and hexamethyldisilazane is 40:240:4:8;
[0122] The particle size of the hydrotalcite is 100 nm;
[0123] The mass ratio of the hydrotalcite, toluene, methyl palmitate and silane-terminated fluorocarbon resin solution is 60:140:5:100.
[0124] Step 3: Preparation of cross-linking agent
[0125] Add diethylenetriamine and acetone to a reaction kettle, then heat and maintain the temperature at 60°C, control the stirring rate to 600 rpm, stir under condensation reflux, then drop 3-isocyanatepropyltrimethoxysilane into the reaction kettle at a rate of 10 g / min, continue to stir and react at a constant temperature for 11 hours, continue to maintain the constant temperature, evacuate and distill under reduced pressure, and remove acetone to obtain a solid that is a co-crosslinking agent;
[0126] The mass ratio of the diethylenetriamine, acetone and 3-isocyanatepropyltrimethoxysilane is 45:270:26.
[0127] Step 4: Preparation of dealcoholized silicone sealant
[0128] The specific formula of the dealcoholized organic silicon sealant for photovoltaic modules is as follows, in parts by weight:
[0129] 240 parts of α,ω-dihydroxy polydimethylsiloxane,
[0130] 35 parts of modified nano calcium carbonate,
[0131] 55 parts of modified hydrotalcite,
[0132] 25 parts of tackifier,
[0133] 3 parts of fumed silica,
[0134] 30 parts of dimethyl silicone oil,
[0135] 1.5 parts of catalyst,
[0136] 4 parts of promoter,
[0137] 20 parts of cross-linking agent,
[0138] 15 parts of auxiliary cross-linking agent;
[0139] The fumed silica is Aerosil-R812 from Degussa, with a surface area of 260 m 2 / g, average particle size is 7nm;
[0140] The tackifier is tetra(2-ethylbutyl)silicate;
[0141] The catalyst is dibutyltin dilaurate;
[0142] The co-catalyst is bis(trimethylsilylmethyl)amine;
[0143] The cross-linking agent is methylsilanetriol;
[0144] According to the specific formula of dealcoholization type silicone sealant for photovoltaic modules in parts by weight, α, ω-dihydroxy polydimethylsiloxane, tackifier, dimethyl silicone oil, catalyst, co-catalyst, cross-linking agent and co-cross-linking agent are put into a dry and water-free double planetary mixer, and the vacuum negative pressure in the double planetary mixer is maintained at -0.09MPa. The stirring rate is controlled at 130 rpm and the dispersion rate is 8500 rpm. After stirring and dispersing for 3 hours, the stirring rate is increased to 180 rpm and the dispersion rate is increased to 10000 rpm, and then fumed silica is added. After stirring and dispersing for 8 hours, modified nano calcium carbonate and modified hydrotalcite are added, and stirring and dispersing is continued for 12 hours to obtain a viscous glue solution. After continuous vacuum degassing, the bubble-free glue solution is discharged and filled into a dry packaging container, which is filled with nitrogen for protection and sealed to obtain the dealcoholization type silicone sealant for photovoltaic modules.
[0145] Example 4: A dealcoholized silicone sealant for photovoltaic modules
[0146] The operations of steps 1, 2, and 3 are the same as those of Example 1;
[0147] Step 4: Preparation of dealcoholized silicone sealant
[0148] The tackifier is tris(trimethylsilyl)borate;
[0149] The other operations are the same as those in Example 1.
[0150] Comparative Example 1: Based on Example 1, step 1, preparation of modified nano-calcium carbonate, is not performed. In step 4, preparation of dealcoholized silicone sealant, 33 parts of modified nano-calcium carbonate are replaced by 33 parts of nano-calcium carbonate. The specific operation is as follows:
[0151] Step 1, preparation of modified nano calcium carbonate is not performed;
[0152] The operations of steps 2 and 3 are the same as those of Example 1;
[0153] Step 4: Preparation of dealcoholized silicone sealant
[0154] Based on Example 1, 33 parts of modified nano calcium carbonate were replaced by 33 parts of nano calcium carbonate, and the other operations were the same as in Example 1;
[0155] The particle size of the nano calcium carbonate is 50 nm.
[0156] Comparative Example 2: Based on Example 1, step 2, preparation of modified hydrotalcite, is not performed. In step 4, preparation of dealcoholized silicone sealant, 45 parts of modified hydrotalcite are replaced by 45 parts of modified nano-calcium carbonate. The specific operation is as follows:
[0157] Step 1: The operation is the same as in Example 1;
[0158] Step 2, preparation of modified hydrotalcite is not performed;
[0159] The operation of step 3 is the same as that of embodiment 1;
[0160] Step 4: Preparation of dealcoholized silicone sealant
[0161] On the basis of Example 1, 45 parts of modified hydrotalcite were replaced by 45 parts of modified nano-calcium carbonate, and other operations were the same as in Example 1.
[0162] Comparative Example 3: Based on Example 1, step 3, preparation of the auxiliary cross-linking agent, is not performed. In step 4, preparation of the dealcoholized silicone sealant, 12 parts of the auxiliary cross-linking agent are replaced by 12 parts of the cross-linking agent in equal amounts. The specific operation is as follows:
[0163] The operations of steps 1 and 2 are the same as those of Example 1;
[0164] Step 3, preparation of a cross-linking agent, is not performed;
[0165] Step 4: Preparation of dealcoholized silicone sealant
[0166] Based on Example 1, 12 parts of the auxiliary cross-linking agent were replaced by 12 parts of the cross-linking agent, and the other operations were the same as in Example 1.
[0167] Comparative Example 4: Based on Example 1, in step 4, in the preparation of dealcoholized silicone sealant, 15 parts of tackifier were replaced with 15 parts of α,ω-dihydroxypolydimethylsiloxane, and the specific operation was as follows:
[0168] The operations of steps 1, 2, and 3 are the same as those of Example 1;
[0169] Step 4: Preparation of dealcoholized silicone sealant
[0170] Based on Example 1, 15 parts of the tackifier were replaced by 15 parts of α,ω-dihydroxypolydimethylsiloxane, and the other operations were the same as in Example 1.
[0171] Performance Test:
[0172] The dealcoholized silicone sealant for photovoltaic modules obtained in Examples 1, 2, 3, 4 and Comparative Examples 1, 2, 3, 4 was tested with reference to GB / T13477.3-2017, GB / T 11211-2009, GB / T528-2009, GB / T531.1-2008, and JG / T465-2014 for surface drying time, 24h curing depth, bonding strength, tensile strength, shear strength, Shore hardness, elongation at break, UV resistance, and moisture and heat resistance. The moisture and heat resistance was tested at 120°C and 100% relative humidity for 24 hours and 48 hours.
[0173] The specific test results are shown in Table 1:
[0174] Table 1
[0175]
[0176] From the test data in Table 1, it can be seen that in Comparative Example 1 where nano calcium carbonate is not modified, the surface drying time is greatly increased, the 24-hour curing depth is greatly reduced, the mechanical properties such as bonding strength, tensile strength, Shore hardness, shear strength and elongation at break are seriously reduced, and the UV resistance and moisture and heat resistance are basically reduced to the lowest value among all embodiments and comparative examples. This shows that if nano calcium carbonate is not surface modified, it is difficult to be uniformly dispersed in the dealcoholized silicone sealant matrix, which seriously affects the various properties of the dealcoholized silicone sealant, especially the moisture and heat resistance. Nano calcium carbonate has a poor performance in the sealant. The internal aggregation of the colloid leads to the existence of an interface between the organic part and the inorganic part after the colloid is cured, which makes it difficult to prevent the penetration of water vapor at high temperature, thereby causing a serious reduction in the moisture and heat resistance. In Comparative Example 2, no modified hydrotalcite is added, and the surface dry time and 24-hour curing depth are slightly reduced, and the mechanical properties such as bonding strength, tensile strength, Shore hardness, shear strength and elongation at break are also reduced. This may be due to the surface of the modified hydrotalcite being coated with a silane-terminated fluorocarbon resin, and the silane-terminated fluorocarbon resin contains unreacted silicon-hydrogen bonds or nitrogen-hydrogen bonds, and these two groups have particularly active cross-linking The reaction activity can promote the cross-linking reaction of the modified hydrotalcite and the organic silica gel. Therefore, after the modified hydrotalcite is replaced by modified calcium carbonate, this cross-linking reaction does not occur, resulting in a decrease in the cross-linking density of the adhesive layer after curing, which in turn causes a significant decrease in the mechanical properties. In addition, the UV resistance and moisture and heat resistance of Comparative Example 2 are both significantly reduced, which shows that the modified hydrotalcite coated with silane-terminated fluorocarbon resin can greatly improve the UV resistance and moisture and heat resistance of the dealcoholized organic silicone sealant; in Comparative Example 3, no auxiliary cross-linking agent is prepared, and no auxiliary cross-linking agent is added to the adhesive formula, and the extent of the extension of the surface drying time is relatively The curing depth after 24 hours is significantly reduced, which indicates that the auxiliary cross-linking agent has a significant effect on improving the reactivity of the colloid. The mechanical properties of Example 3, such as bonding strength, tensile strength, Shore hardness, shear strength and elongation at break, have decreased relatively greatly, which indicates that the auxiliary cross-linking agent affects these mechanical properties by affecting the cross-linking degree of the colloid curing process. In addition, the UV resistance and moisture resistance of Example 3 also have a significant decrease, which indicates that the auxiliary cross-linking agent affects the UV resistance of the entire adhesive layer and the mechanical property retention rate under high temperature and high humidity by affecting the cross-linking density of the adhesive layer after curing.In comparative example 4, no tackifier is added, and the surface drying time increases to the longest, and the 24-hour curing depth decreases to the lowest, which shows that the tackifier is very important for enhancing the reactivity of the colloid formula. The bonding strength of comparative example 4 decreases to the lowest, and the tensile strength, shear strength and elongation at break also decrease extremely sharply, which shows that the tackifier promotes the reactivity of the colloid while also improving the mechanical properties of the adhesive layer after curing. The reduction in the UV resistance and moisture resistance of comparative example 4 is also very large, which may be because after the adhesive layer is cured, the bonding force with the surface of the bonded substrate is insufficient, which makes it easy for light and high heat and humidity to invade the interior of the adhesive layer, so that after the adhesive layer is cured, it is easy to lose mechanical properties in extreme test environments. ;
[0177] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A dealcoholized silicone sealant for photovoltaic modules, characterized in that: The specific formula of the dealcoholized organic silicon sealant for photovoltaic modules is as follows, in parts by weight: 170-240 parts of α,ω-dihydroxy polydimethylsiloxane, 25~35 parts of modified nano calcium carbonate, 30~55 parts of modified hydrotalcite, Thickener 10~25 parts, 1~3 parts of fumed silica, 15-30 parts of dimethyl silicone oil, 0.2~1.5 parts of catalyst, 1~4 parts of co-catalyst, Cross-linking agent 11~20 parts, 8-15 parts of auxiliary cross-linking agent; The fumed silica is Aerosil-R812 from Degussa, with a surface area of 260 m 2 / g, average particle size is 7nm; The tackifier is one of bis(sec-butyl)orthosilicate triethylaluminum orthosilicate, tetra(2-methoxy-1-methylethyl) silicate, tetra(2-ethylbutyl) silicate, and tri(trimethylsilyl)borate; The catalyst is dibutyltin dilaurate; The co-catalyst is one of bis(trimethylsilylmethyl)amine and O-(trimethylsilyl)hydroxylamine; The cross-linking agent is one of methylsilanetriol and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine; The modified nano calcium carbonate has a preparation method comprising: drying the nano calcium carbonate at 110-135°C for 10-20 hours, placing the nano calcium carbonate in a dry and water-free sealed high-speed dispersion kettle, adding anhydrous ethanol, heating and maintaining the temperature at 60-80°C, dispersing vigorously at a speed of 7000-10000 rpm for 6-12 hours, reducing the speed to 1500-3000 rpm, adding 3,3,3-trifluoropropyltriethoxysilane, reacting at a constant temperature for 8-15 hours, cooling to room temperature, discharging, centrifuging, and drying the obtained solid in a vacuum oven at 60-75°C for 5-11 hours to obtain the modified nano calcium carbonate; The modified hydrotalcite is prepared by adding fluorocarbon resin, toluene and triethylamine into a reaction kettle, controlling the stirring rate at 400-800 rpm, heating and maintaining the temperature at 120-150°C under nitrogen protection, adding hexamethyldisilazane into the kettle under condensation reflux and nitrogen protection, and after the addition is completed, stirring and reacting at a constant temperature for 6-11 hours, cooling to obtain a silane-terminated fluorocarbon resin solution, and then drying the hydrotalcite at 120-140°C for 10-16 hours, adding it into a dispersion kettle, and then condensing and refluxing. Toluene and methyl palmitate are added into the kettle, and the dispersion rate is controlled to be 5000-9000 rpm. After strong dispersion for 8-14 hours, the temperature in the kettle is raised and kept constant at 100-130° C., and the dispersion rate is reduced to 1000-3000 rpm. Then, a silane-terminated fluorocarbon resin solution is added, and the reaction is dispersed and stirred under condensation reflux for 6-13 hours, and then centrifuged. After the separated solid is washed with anhydrous ethanol for 3-5 times, it is placed in a vacuum oven at 50-80° C. and dried for 6-13 hours to obtain a modified hydrotalcite. The fluorocarbon resin has a fluorine content of 30-40 wt %, a number average molecular weight of 1000-4000 g / mol, a viscosity of 200-900 mPa·s, a hydroxyl value of 40-65 mgKOH / g, and an acid value of 1.0-2.5 mgKOH / g; The preparation method of the auxiliary cross-linking agent is as follows: diethylenetriamine and acetone are added to a reaction kettle, and then the temperature is raised and kept constant at 40-60°C, the stirring rate is controlled at 300-600 rpm, and 3-isocyanatepropyltrimethoxysilane is added dropwise to the reaction kettle at a rate of 1-10 g / min under stirring, condensation and reflux, and after the addition is completed, the reaction is continued at a constant temperature and stirred for 5-11 hours, and then the temperature is maintained continuously, vacuum distillation is performed, and after acetone is evaporated, the obtained solid is the auxiliary cross-linking agent.
2. The dealcoholized organic silicon sealant for photovoltaic modules according to claim 1, characterized in that: The particle size of the nano calcium carbonate is 10-60 nm; The mass ratio of the nano-calcium carbonate, anhydrous ethanol and 3,3,3-trifluoropropyltriethoxysilane is 25-45:150-190:3-9.
3. The dealcoholized organic silicon sealant for photovoltaic modules according to claim 1, characterized in that: In the preparation of the silane-terminated fluorocarbon resin solution, the mass ratio of fluorocarbon resin, toluene, triethylamine, and hexamethyldisilazane is 15-40:140-240:1-4:3-8; The particle size of the hydrotalcite is 30-100 nm; The mass ratio of the hydrotalcite, toluene, methyl palmitate and silane-terminated fluorocarbon resin solution is 30-60:50-140:1-5:40-100.
4. The dealcoholized silicone sealant for photovoltaic modules according to claim 1, characterized in that: The mass ratio of the diethylenetriamine, acetone and 3-isocyanatepropyltrimethoxysilane is 15-45:110-270:8-26.
5. The dealcoholized silicone sealant for photovoltaic modules according to claim 1, characterized in that: The dealcoholization type organic silicon sealant is prepared by: according to the specific formula of the dealcoholization type organic silicon sealant for photovoltaic modules in parts by weight, α,ω-dihydroxy polydimethylsiloxane, tackifier, dimethyl silicone oil, catalyst, co-catalyst, cross-linking agent, and co-cross-linking agent are placed in a dry and water-free double planetary mixer, the vacuum negative pressure in the double planetary mixer is maintained at -0.1 to -0.09 MPa, the stirring speed is controlled at 90 to 130 rpm, and the dispersion speed is controlled at 6000 to 8500 rpm. After stirring and dispersing for 1 to 3 hours, the stirring rate is increased to 140 to 180 rpm and the dispersion rate is increased to 9000 to 10000 rpm, and then fumed silica is added. After stirring and dispersing for 5 to 8 hours, modified nano calcium carbonate and modified hydrotalcite are added, and stirring and dispersing is continued for 6 to 12 hours to obtain a viscous adhesive solution. After continuous vacuum degassing, the bubble-free adhesive solution is discharged and filled into a dry packaging container, which is filled with nitrogen for protection and sealed to obtain a dealcoholized silicone sealant for photovoltaic modules.
Citation Information
Patent Citations
Moisture-resistant and heat-resistant high-strength silicone structural adhesive special for photovoltaic assemblies
CN107880797A
Silicone adhesive for photovoltaic module frame as well as preparation method and application of silicone adhesive
CN117467400A
Dealcoholized sealant with long storage stability and preparation method of dealcoholized sealant
CN104293231A
Dealcoholized photovoltaic module sealant and preparation method thereof
CN113337245A